DEVELOPING LANGUAGE ASPECTS IN MENTIONING LETTER SYMBOLS IN GROUP B OF NURUTTAQWA KINDERGARTEN BANJARMASIN - setyana Oktavia; Akhmad Riandy Agusta (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2023)
This research was motivated by the lack of development of children's ability to mention letter symbols caused by the media used by teachers in the learning process to recognize letters that did not attract children's hearts, thus making children less enthusiastic and not eager to participate in learning activities. The purpose of this study is to improve and improve the quality of the learning process of group B in Nuruttaqwa Kindergarten Banjarmasin. This research approach uses qualitative and quantitative approaches with the type of classroom action research (PTK) held 4 meetings. Techniques for collecting observations of teacher activities, observation of children's activities, children's learning outcomes, language skills. The results showed that teacher activity increased with a score of 25 criteria